Dasatinib suppresses atherosclerotic lesions by suppressing cholesterol uptake in a mouse model of hypercholesterolemia - Masamitsu Takaba; Takayuki Iwaki; Tomohiro Arakawa; Takaaki Ono; Yuichiro Maekawa; Kazuo Umemura (Elsevier, 2022)
Although the use of BCR-ABL1 tyrosine kinase inhibitors (TKIs) for chronic myeloid leukemia is known to cause vascular adverse events (VAEs), the frequency of VAEs during dasatinib administration is not high, and the same holds for atherosclerosis-related VAEs. However, its effect on atherosclerosis remains controversial. In this study, our primary objective was to investigate how dasatinib affects atherosclerosis. Ldlr−/−/Apobec1−/− mice, which are highly prone to develop atherosclerosis, were administered dasatinib. After 16 weeks, we evaluated their atherosclerotic lesions. We used bone-marrow-derived macrophages to investigate the uptake of oxidized low-density lipoprotein (LDL) complexed with DiI dye (DiI-oxLDL). RNA sequencing and quantitative reverse transcription polymerase chain reaction (RT-qPCR) were performed to explore the potential effects of dasatinib on cholesterol metabolism. Dasatinib administration significantly reduced atherosclerotic lesions (P < 0.001 and P = 0.013) and DiI-oxLDL uptake (P < 0.001) unlike other TKIs. RNA sequencing and RT-qPCR suggested that Sort1, which encodes sortilin, a known regulator of LDL uptake, and Cd36 were potential targets of dasatinib. In conclusion, dasatinib induced elevated LDL-C levels, but oxLDL uptake in macrophages were suppressed, resulting in reducing atherosclerotic lesions. These results further our understanding of the differences in VAEs between dasatinib and other TKIs.